Frecuency and characteristics of obese subjects with and without cardiometabolic risk - Garmendia, Fausto (2018)
Objetive. To study the frequency and characteristics of an obese population with and without cardiometabolic risk (CMR) and, to revise the concept of cardiometabolically healthy obese CMHO subjects. Material and methods. A total of 105 obese subjects, 30 to 75 years old, were recluted from a preventive-promotional program from may 2015 to april 2016. Previous informed consent, age, gender, anthropometric measures, blood pressure (BP), personal and family history of cardiovascular risk factors (CVRF) were registered. At fasting glucose (G), total cholesterol (TC), HDL cholesterol (cHDL), triglycerides (Tg), creatinine, plasma proteins, bilirrubins, transaminases (AST,ALT), alkaline fosfatase (FA) and gamaglutamyltranspeptidase (GGTP) were measured in blood by conventional methods. VLDL, LDL, Non-HDL fractions were calculated. Statistics were calculated with SPSS.23 program. Results. 77,4% were women, mean age 51±0,86 years. Women had lower height, weight and abdominal circumference than male but higher HDL concentration, other parameters were similar. Obesity grade I was found in 45,7%, grade II in 24,7% and grade III in 29,5%. Dislipoproteinemia had 89,2% of women and 87% of men; high blood pressure (HBP): women 20,7%, men 21,4%; tobaccoism women 5,5%, male 42,3%; hyperglycemia: women 14,2%, men 14,2%; macrosomia/low birthweight: women 6,94%, men 0%; elevated hepatic enzymes: women 29,8%, male 32,1%. 9,52% were CMHO since they had normal BP, G. HDLc, Tg, LDLc and Non-HDL . Conclusions. The majority of obese patients had CMR, only 10 (9,5%) were CMHO.